Draft-free air conditioning through split membrane ceiling system: An exploratory study - Shaoyu Sheng; Toshio Yamanaka; Tomohiro Kobayashi; Narae Choi; Shuji Yodono (Elsevier, 2024)
The draft caused by convective air-conditioning is a primary contributor to thermal discomfort, particularly in localized cooling scenarios. While radiant systems offer a windless alternative, their condensation risks and maintenance costs bring concerns. In response, our research proposes an air-based radiation-convection hybrid system that's draft-free and easy to implement. By suspending a breathable, flexible, textile-based membrane beneath the ceiling, the system mitigates drafts from ceiling-mounted air conditioners and leverages the membrane's vast surface area for radiation. This work is an exploratory study focused on a retrofit split membrane system laying below the commercially packaged air conditioner (PAC). Three independent experimental studies were conducted. The first is a full-scale experiment assessing the membrane's impact on PAC system operation and heat load management. The second is fundamental research to determine the permeation and airflow deceleration properties of different membranes. The third is a practical assessment in a self-study room retrofitted with the split membrane, aiming to determine the possibility of maintaining draft-free conditions. Results indicate that membranes with high laying ratios risk airflow short-circuiting. It can be reduced by adjusting the laying ratios and altering the laying pattern of the membrane, which also improves perimeter heat load management. Moreover, the permeation characteristics of various membrane materials were examined through flow and velocity attenuation coefficients. Besides material considerations, preliminary observations suggest that the membrane's curvature could influence its permeation. Furthermore, the temperature and velocity data preliminarily affirmed the anti-draft performance of the split membrane ceiling system.